Increasing Knowledge Of Pramenstrual Syndrome In Teenage Girls During Covid-19 Pandemic - Maria Floriana Ping; Elfina Natalia (Wadah Inovasi Indonesia, 2022)
COVID-19 was declared a national disaster on February 29, 2020, the government recommends that all health services focus on and prioritize handling COVID-19 and other health problems that are considered medical emergencies. Changes in health service priorities decreasing Sexual and Reproductive Health (KSR) services that are not included in medical emergency services. This restriction certainly makes it difficult for adolescents who need direct services such as STI checks or other reproductive health complaints (Sutrisna, 2020). Problems regarding menstruation are a problem for most women in Indonesia (38.45%) (Damayanti, 2013; Yunita et al, 2021). Service activities carried out online using an application attended by 90 junior high school students were health counseling activities regarding health education for young women: premenstrual syndrome. At the end of the activity, it was found that the majority of the levels of premenstrual syndrome experienced by 43 participants (47.8%) were moderate.